Taxation In Society For Development And Welfare Taxation In Society For Development And Welfare - Prawitasari , Andriyani; Yodista, Yodista; Hidayah , Nenden Restu (Journal of Law, Social Science, and Management Review, 2025)
Taxation plays a crucial role in supporting development and welfare in socienty. As a primary source of government revenue, taxes are used to finance various sectors such as infrastructure, education, healthcare, and public services. Proper tax management can ensure equal access to quality basic services, reduce social inequalities, and create employment opportunities. Additionally, taxation contributes to the economic stability of the country. This article discusses how taxation can enhance devalopment and welfare, as well as the importance of active participation from society in a fair and transparent tax system.